Isoinertial and Isokinetic Sprints: Muscle Signalling - Fuentes, T.; Ponce-González, J. G.; Morales-Alamo, D.; de Torres-Peralta, R.; Santana, A.; De Pablos-Velasco, P.; Olmedillas, H.; Guadalupe-Grau, A.; Rodríguez-García, L.; Serrano-Sanchez, J. A.; Guerra, B.; Calbet, J.A. L. (International Journal of Sports Medicine, 2013)
To determine if the muscle signalling response to a 30 s all-out sprint exercise is modulated by the exercise mode and the endocrine response, 27 healthy volunteers were divided in 2 groups that performed isokinetic (10 men and 5 women) and isoinertial (7 men and 5 women) Wingate tests. Blood samples and vastus lateralis muscle biopsies were taken before, immediately after, 30 and 120 min after the sprints. Groups were comparable in age, height, body weight, percentage of body fat, peak power per kg of lower extremities lean mass (Pmax) and muscle fibre types. However, the isoinertial group achieved a 25% greater mean power (Pmean). Sprint exercise elicited marked increases in the musculus vastus lateralis AMPKα, ACCβ, STAT3, STAT5 and ERK1/2 phosphorylation (all P<0.05). The AMPKα, STAT3, and ERK1/2 phosphorylation responses were more marked after the isoinertial than isokinetic test (interaction: P<0.01). The differences in muscle signalling could not be accounted for by differences in Pmax, although Pmean could explain part of the difference in AMPKα phosphorylation. The leptin, insulin, glucose, GH, IL-6, and lactate response were similar in both groups. In conclusion, the muscle signalling response to sprint exercise differs between isoinertial and isokinetic sprints.
Keywords: Wingate; sprint exercise; muscle signalling; leptin